Product Analysis of Micro, Small and Medium Enterprises of Bankziska Partner Lazismu Ngrayun Ponorogo: Analilis Produk Usaha Mikro Kecil dan Menengah Mitra Bankziska Lazismu Ngrayun Ponorogo - Rois, Adib Khusnul; Susanto, Happy; Sudarmadi, Sudarmadi; Laily, Gabriel (Perisai : Islamic Banking and Finance Journal, 2025)
This study discusses the empowerment of the Community's economy carried out by BankZiska Lazismu Ngrayun with Micro, Small, and Medium Enterprises partners in Selur Village using the Qardhul Hasan program. The background of this study is that many small and medium enterprises in Selur Village are trapped in bank loans, making it difficult for them to develop their businesses. The income they earn is used to pay off the debts of loan sharks who ensnare them every day. Therefore, company management is only static and difficult to develop. The presence of BankZiska Lazismu helps small and medium enterprises escape the trap of usury and usury loans. Those who may be trapped and affected by usury can be helped by the Qardhul Hasan loan. The research method used is qualitative with a case study approach, data collected through interviews, observations, and documentation from the director of BankZiska Lazismu Ngrayun and Micro, Small, and Medium Enterprises partners of BankZiska. The results of the study show that BankZiska Lazismu Ngrayun is very helpful for Micro, Small, and Medium Enterprises to develop their businesses and provide financial assistance with the Qardhul Hasan system. Partners funded by BankZiska There are approximately 50 BankZiska partners in Ngrayun, the products produced by Micro, Small, and Medium Enterprises partners of BankZiska there include: instant tiwul, instant Gatot, instant turmeric, instant ginger, palm sugar, gadung chips, taro chips, tempeh chips, these products are typical food souvenirs from Ngrayun sub-district.